Preparing students to apply transversal skills a case study in higher education – 2nd phase - Almeida, F.; Rocha, H. B.; Casquilho-Martins, I. (WCES2018 - 10th World Conference of Education Sciences, 2018)
A diverse vocational offer, with a stronger emphasis on key competences, including transversal ones, can provide much needed routes for individuals to improve their qualifications and thus access the labour market. One of the main purposes of the current education and learning efforts is to equip students with competences that are transferable across contexts and that lie beyond approaches to content or areas of knowledge. This study goes through two phases, the first one already published, aimed to devise a profile of transversal skills of the education professional, able to guide the training work in the higher education institutions, support the tasks of evaluation and certification of the said competences and promote the personal and professional development of 1st cycle students A focus group was guide structured based on the objective of this exploratory study (Teaching, learning and evaluation strategies that differentiate the teacher of transversal competences), had five questions and was applied to the traversal skills teachers. The Profile was developed around the following key values and areas of competence: Valuing diversity - difference is considered a resource and a value for education; Working with others - collaboration and teamwork are essential methodologies for all teachers; Professional and personal development - teaching is a learning activity and teachers are responsible for a lifelong learning and Participation - means that all students are involved in learning activities that are meaningful to them. Access to higher education alone is not enough. In this second phase, based on the results previously found, we try to know the perception that the students of transversal competences courses have about this question. To do this, and based on the variables previously identified, we inquired a sample of students, to compare the results obtained with those of the 1st phase and also add to the results of the 1st phase perception about this issue. This study improves the identification and characterization of the requirements to teach transversal competences, and contributes to improve the processes of teacher selection and training.